Reconceptualizing Salam Contracts: A Flexible Sharia-Compliant Framework for Modern Islamic Banking - Kautsar Riza Salman; Entis Sutisna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study proposes a conceptual framework for an enhanced Salam contract model aimed at improving flexibility, operational efficiency, and practical relevance within contemporary Islamic banking. Although Salam is a Shariah-compliant forward sale contract with strong jurisprudential foundations, its institutional application remains limited due to contractual rigidity, sectoral restrictions, and operational challenges. Drawing on a systematic review of literature published between 2016 and 2026, this paper identifies key constraints in existing Salam practices, including narrow usage confined primarily to agricultural commodities, limited practitioner familiarity, and risk management concerns. In response, the study develops a conceptual model that extends Salam applicability to a broader range of goods and services meeting clearly defined specifications and introduces a structured price-adjustment mechanism that allows buyers to request discounts when delivered goods fail to meet agreed standards. This innovation is expected to reduce dispute risk, enhance legal certainty, and strengthen fairness principles in Shariah-compliant transactions. From a practical perspective, the proposed model has the potential to improve liquidity management, support product innovation—including digital and parallel Salam structures—and enhance institutional competitiveness.